The application of artificial neural networks in optimization of heat treatment processes of steel - Wołowiec, Emilia; Kula, Piotr (Wydawnictwo Politechniki Łódzkiej, 2011)
This article is dedicated to processes of vacuum carburization, which constitute an alternative method to industrial multi-segment carburization. Special attention has been paid to the possibility of using artificial neural networks to design processes of such type. The following subchapters deal with the essence and purposes of vacuum carburization, the course of research on processes and the possibility of using neural networks to design such processes, and the architecture of a sample neural network which achieves this goal.